1989
DOI: 10.1161/01.res.64.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced energy metabolism and reperfusion on the permeability and morphology of the capillaries of an isolated rete mirabile.

Abstract: The effects of reduction in energy metabolism were explored in the eel rete mirabile, an organ composed predominantly of capillaries. In vitro experiments showed that glycolysis is the major pathway of energy production in this capillary tissue, and that iodoacetate, KCN, and low PO j in combination markedly reduce its ATP generation. When in situ energy generation was inhibited by this combination during countercurrent perfusion of the arterial and venous capillaries of the rete, an approximate doubling of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…We were able to inhibit the development of the double ring pattern by perfusing the capillary bed with phalloidin prior to ischaemia. Phalloidin enhances actin polymerisation, stabilises actin filaments [20, 21, 34]and has been shown not to affect endothelial cell viability, growth or metabolism [16, 17, 22]. Phalloidin does not target β-actin [8, 28, 35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were able to inhibit the development of the double ring pattern by perfusing the capillary bed with phalloidin prior to ischaemia. Phalloidin enhances actin polymerisation, stabilises actin filaments [20, 21, 34]and has been shown not to affect endothelial cell viability, growth or metabolism [16, 17, 22]. Phalloidin does not target β-actin [8, 28, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence, including the initiation of a reorganisation of the cell surface area by various vasoactive substances, suggests that capillary endothelial cells possess the potential to contribute to changes in luminal dimensions [10, 11, 12, 13, 14, 15]. Reorganisation of the endothelial microfilament system may be induced by many vasoactive chemicals [16, 17, 18]. Glyn and Ward [19]demonstrated focal narrowings in resin casts of capillaries and used phalloidin to prevent the changes of capillary dimensions which occur during reperfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that inhibition of energy metabolism and arrest of flow, followed by reperfusion, induces substantial structural and functional changes in the rete. 6 Other in vitro studies have suggested that reduced ATP generation results in restructuring and loss of actin filaments in endothelial cells. 14 -15 Therefore, normal and reperfused rete preparations were used in this study, with the idea that phalloidin might maintain the microvascular barrier through stabilization of cellular cytoskeletal micronlaments.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that this procedure combines the effects of arrest of both energy generation and flow. 6 Finally, the retia were reperfused with oxygenated control medium for 1 hour. The protocol was then repeated with six other retia in similar fashion, except that the perfusion medium throughout the experiment contained 10" 6 M phalloidin.…”
Section: Permeability Studiesmentioning
confidence: 99%